(untitled) (Global Journal of Management and Business Research, 2014)
The study examined the economics of catfish production in Akwa Ibom State, Nigeria. Data for the study were obtained from 120 catfish farmers in Akwa Ibom State using multi-stage sampling procedure, and analyzed using descriptive statistics and budgeting technique. Results show that 36.7% of the respondents were aged between 41-50 years with 85.8% being married and 80% having formal education. The costs and returns analysis indicates that the fixed cost constituted 65.37% of the total cost of production while the variable cost constituted 34.63%. The total cost of catfish production was N37, 845,240.00; the total revenue was N56, 385,000.00 and the net income was N18, 539,760.00 indicating that catfish production was profitable in the study area. Findings also reveal that high cost of feeds, high cost of pond construction and lack of capital/finance were the most severe constraints to catfish farming in Akwa Ibom State, Nigeria. It is recommended that prices of feeds and access to feeds be regulated by the State Government in order to reduce the problems of high cost of feeds/inadequate supply of feeds to catfish farmers in the State.